MADRASAH'S CONTRIBUTION TO THE EMPOWERMENT OF THE VILLAGE COMMUNITY IN INDONESIA - Rt Bai Rohimah; Muhammad Mahfud; Opan Arifudin; Suhana Sarkawi (Adisam Publisher, 2024)
The study aims to examine the contribution of Madrasah to empowerment of rural communities in Indonesia. Research methods carried out through literary methods by searching for literature that fits the context of research. Research findings show that the presence of Islamic educational institutions, the Madrasah that exists in the village, turns out to play a significant role in improving the capacity and well-being of individuals through various educational programmes and social activities. Collaboration with various stakeholders and the involvement of the local community is the key to success in empowering the village community. It is hoped that these findings can be the basis for further enhancing the role of Madrasah in supporting the empowerment of the village community in Indonesia.